Remembering media and journalism in socialist Yugoslavia - Kaluža, Jernej (Prispevki za novejšo zgodovino, 2022)
In recent decades, memory studies have become a prominent interdisciplinary field of research, with several studies focusing on the specifics of socialist Yugoslavia and its demise. Less attention, however, has been paid to the media and journalism in the life and functioning of the state. This study explores what role these central social institutions played in every-day lives of the population, what level of trust they enjoyed amongst them, and how they influenced the processes of forming collective and individual memory in socialist Yugoslavia. We consider these issues by analysing 96 semi-structured oral history interviews with media audiences. The interviewees had personal recollections of this era since they lived in socialist Yugoslavia for most of their lives and could thus provide unique and valuable insights not available by other means. Interpretative analysis was performed with deductive coding of the interviews and was separated into three parts: everyday media use; trust in the media and journalism; and perceptions of socialist Yugoslavia. This paper presents a short overview of the dataset and indicates its potential value for future research. The gathered data also reveal the interviewees’ understanding and evaluation of the Yugoslav regime and, in general, provide a much more nuanced view of the socialist past than is most often found in today’s polarised public debates.
Keywords: Kolektivni spomin; Mediji; Novinarstvo; Občinstvo; Socializem; spominske študije; tematizirane življenjske zgodbe; uporaba medijev; Ustna zgodovina; zgodovina novinarstva